AN ANALYSIS OF THE SYMBOLS OF LOVE, LIFE, AND DEATH IN KAHLIL GIBRAN'S POEMS - Rima Sarah (Jurnal Adabiya, 2021)
Kahlil Gibran is a Lebanese-American artist, writer, and poet. He is no stranger to literary lovers and connoisseurs. His phenomenal works made Kahlil Gibran famous. His life experience also adds its unique value to his works. The various meanings hidden behind each of his works deserve further analysis. Some of them are typical poems from Kahlil Gibran. He has his way of expressing the true meaning of life through his poems. Therefore, this study will show the symbolic meaning of these poems by using the hermeneutical analysis method from Paul Ricoeur. This method explains the meaning of the symbol in real life. A symbol is a form that gives meaning to every word or sentence contained in a literary work. The result of this analysis is the discovery of various kinds of symbols contained in the poems by Kahlil Gibran, including symbols of love, life, and death. Based on these findings, it can be concluded that love, life, and death are some of the symbols found in Kahlil Gibran's poems.